Purchase of Development Rights (PDR) Mechanism Application on Cost-Benefit Sharing Principles - Endang Hernawan; Hariadi Kartodiharjo; Dudung Darusman; Sudarsono Soedomo (Institut Pertanian Bogor (IPB University), 2010)
Although North Bandung Area was considered as protected area and watershed area uspstream, but it has characteristic as cultivation and downstream area. An effort to improve protection function is needed to prevent changes in land use. One of them through the purchase of development rights (PDR) mechanism. The appropriateness of the PDR application on the benefit of hydrology only effective when it was carried out in zone rural area and the rural fringe. This condition was caused by land prices which exceeded from landexpetation value, therefore the owner of the land experienced impermanence syndrome. The application of Cost-Benefit Sharing Principles would helped Government of the Bandung City in the aspect of the purchace of development right for the agricultural land in KBU that entered Kabupaten Bandung Barat and Kabupaten Bandung. Whereas, for the Cimahi City it helped the purchase of development right for agricultural land in KBU that entered Kabupaten Bandung Barat.